Developing Telecommunications eLearning modules: Flexible performance support - Sandler, John (International Journal of Advanced Corporate Learning (iJAC), 2008)
This article, in conjunction with a presentation at ICELW 2008 in New York, 12-13 June 2008, explores the successful application of eLearn development methodologies, planning processes, and a user-centred design consultative process. This development approach was applied during 2007, and continues through 2008, together with innovative and effective use of the Telstra eLearn platform, enabling the delivery of highly successful performance support solutions for Telstra field and technical support staff around Australia during 2007 and 2008. The integration of simulation and interaction into competency and learning checks, ensures that Telstra Corporationâ??s field work staff remain competent and capable of supporting emerging and changing technologies as continual enhancements keep being deployed to Telstra 3G networks to benefit customers in all facets of Australian life across the vast expanses of the country.